From FINGER to MET‐FINGER: metformin and lifestyle intervention for multimodal precision prevention of dementia. (20th December 2022) - Kivipelto, Miia; Barbera, Mariagnese; de Jager, Celeste A; Lehtisalo, Jenni; Levak, Nicholas; Middleton, Lefkos T; Price, Geraint J; Rydström, Anders; Thunborg, Charlotta; Mangialasche, Francesca; Ngandu, Tiia; Solomon, Alina
Abstract: Background: The positive results of the landmark Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability ‐ FINGER, 2‐year lifestyle‐based intervention and up to 11 years follow‐up ‐, followed by the Multimodal Preventive Trial for Alzheimer's Disease ‐ MIND‐ADmini, 6‐month lifestyle‐based + medical food, up to 1‐year follow‐up ‐, provided the foundation to advance multimodal trials for dementia prevention within the World‐Wide FINGERS (WW‐FINGERS) network. Innovative trials should involve tailored approaches, combining non‐pharmacological and pharmacological interventions, to optimize interventions´ adherence and efficacy. Method: Through a drug‐repurposing approach, metformin has been identified as a potential disease‐modifying drug for Alzheimer´s disease (AD) and dementia in subjects without type‐2 diabetes, with a robust pharmacological safety profile. Analysis on genetic factors ( APOE, AD Polygenic‐Risk‐Score) and intervention effects from the FINGER trial indicated clear cognitive benefits in participants with genetic susceptibility to AD and dementia. Feasibility data (adherence, retention rate) from FINGER and MIND‐ADmini, including extended follow‐up data analysis, have informed the upgrade of the lifestyle‐based intervention implemented in MET‐FINGER. Result: An update on the trial status will be presented. The MET‐FINGER phase‐IIb trial population includes an APOE ‐enriched population of 600 subjects aged 60‐79 years, with increased risk of dementia due to modifiable risk factors. Participants are recruited in three countries (Finland, Sweden, United Kingdom), and randomized to either an upgraded FINGER lifestyle‐based intervention, alone or in association with metformin (up to 2000mg/day), or the reference group, which follows a self‐guided lifestyle program. MET‐FINGER trial outcomes are harmonized with WW‐FINGERS guidelines, and include cognition and biological measures to detect disease‐modifying effects of metformin. Conclusion: MET‐FINGER pioneering trial leverages and expands on successful experiences from WW‐FINGERS core trials, embodying the next generation of clinical trials for dementia risk reduction and prevention within the framework of precision prevention. The MET‐FINGER trial protocol is the first in its kind, providing the basis for forthcoming trials combining non‐pharmacological and pharmacological interventions. MET‐FINGER results can inform AD drug development and reduce intervention failure rate of new trials.